Mosque Economic Empowerment through Sharia Microfinance Institutions - Yaman, Afdhal (Balai Diklat Keagamaan Ambon, 2024)
Mosques are not only places of worship but also places of economic activity. The potential for economic empowerment in mosques has not been realized optimally. As part of strengthening the community's economy, the role of mosques in society needs to be expanded. So, this research aims to determine the role of mosque economic empowerment through Sharia microfinance institutions. This qualitative research is a literature study using data sources like reference books and scientific journal articles. The results of this research indicate that mosque-based community economic empowerment is necessary as a driving force for poverty alleviation efforts to improve the community's quality of life. Mosques' financial independence can be realized by establishing Islamic Cooperatives or Baitul Maal wa Tamwil (BMT). By maximizing the function and potential of mosques, the Mosque's economy can be strengthened and used as a strategic location for the local community's economic development.